Decellularized sturgeon cartilage extracellular matrix scaffold inhibits chondrocyte hypertrophy in vitro and in vivo. (1st June 2021) - Li, Yongsheng; Chen, Wei; Dai, Yao; Huang, Yuting; Chen, Zongming; Xi, Tingfei; Zhou, Zheng; Liu, Hairong
Abstract: Since chondrocyte hypertrophy greatly limits the efficiency of cartilage defects repairing via cartilage tissue engineering (CTE), it is critical to develop a functional CTE scaffold able to inhibit chondrocyte hypertrophy during this period of cartilage regeneration. In this study, we tested the applicability of using decellularized sturgeon cartilage ECM (dSCECM) scaffold to cease chondrocyte hypertrophy during cartilage damage repair. The dSCECM scaffolds with interconnected porous structure and pore size of 114.1 ± 20.9 μm were successfully prepared with freeze‐dry method. Chondrocytes displayed a round shape and aggregated to form cellular spheroids within dSCECM scaffolds, which is similar to their chondrocytic phenotype within cartilage in vivo. Higher transcriptional level of chondrogenic related genes and integrin related genes was observed in chondrocytes incubated with dSCECM scaffolds instead of type I collagen (COL I) scaffolds, which were used as the control due to their widely usage in CTE and clinic applications. Furthermore, it confirmed that, compared with COL I scaffolds, dSCECM scaffolds significantly reduced the transcription of chondrocyte hypertrophy related genes in chondrocytes following the hypertrophic induction treatment. To test the ability of dSCECM scaffold to inhibit chondrocytes hypertrophy in vivo, chondrocytes with dSCECM scaffolds and COL I scaffolds were cultured with hypertrophic media and were implanted into nude mice respectively. Following 4 weeks implantation, interestingly, only the specimens derived from COL I scaffolds displayed consequences of chondrocyte hypertrophy like calcification deposition, demonstrating that chondrocyte hypertrophy is ceased by the dSCECM scaffold following hypertrophic induction. It suggests that the dSCECM scaffold can be potentially applied in clinical treating cartilage defects via the CTE approach to avoid the risk of chondrocyte hypertrophy.